2014
DOI: 10.1016/j.pmrj.2014.06.012
|View full text |Cite
|
Sign up to set email alerts
|

Contralateral Antalgic Effect of High‐Frequency Transcutaneous Peripheral Nerve Stimulation

Abstract: The present study demonstrates an analgesic effect of HF-TPNS not only in the ipsilateral but also in the contralateral side of stimulation, suggesting a possible role of contralateral HF-TPNS in the treatment by physical therapy of patients with unilateral pain syndromes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…However, local stimulation, i.e., chronic electrical stimulation on the facial nerve induced hyperactivity of the facial nucleus ( 45 ), which may aggravate spasms. In terms of pain relief, local and distal stimulation with acupuncture ( 46 ), transcutaneous peripheral nerve stimulation ( 47 ), or vibratory stimulation ( 48 ) also showed a strong analgesic effect, but differed in stimulus parameters, such as intensity and frequency ( 47 , 48 ). What's more, stimuli at distal or local acupoints can change the excitability in specific brain regions.…”
Section: Discussionmentioning
confidence: 99%
“…However, local stimulation, i.e., chronic electrical stimulation on the facial nerve induced hyperactivity of the facial nucleus ( 45 ), which may aggravate spasms. In terms of pain relief, local and distal stimulation with acupuncture ( 46 ), transcutaneous peripheral nerve stimulation ( 47 ), or vibratory stimulation ( 48 ) also showed a strong analgesic effect, but differed in stimulus parameters, such as intensity and frequency ( 47 , 48 ). What's more, stimuli at distal or local acupoints can change the excitability in specific brain regions.…”
Section: Discussionmentioning
confidence: 99%
“…It was reported that subcutaneous electrical stimulation reduced not only ipsilateral but also contralateral spontaneous and evoked activity of nociceptive dorsal horn cells (Garrison & Foreman, 2002). Studies of healthy humans also revealed that TENS administration reduced pressure pain and heat pain on the contralateral side (Buonocore, Camuzzini, Dall'Angelo, Mandrini, & Toffola, 2015;Claydon et al, 2008). However, the analgesic mechanisms underlying contralateral TENS remain unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Additional studies using experimental human-pain models have shown that TENS applied to one side of the body evokes an analgesic response in the homologous region on the contralateral side. 28,113,114,[117][118][119][120][121][122] Buonocore et al showed that TENS applied to the cutaneous distribution of the superficial radial nerve increased the heat-pain threshold in the dorsal hand bilaterally. 117 Lehmann and Strian showed that both ipsilateral and contralateral TENS reduced tonic thermal pain relative to placebo.…”
Section: Experimental Human Painmentioning
confidence: 99%